Conciliation: application in syariah court - Ali Mohamed, Ashgar Ali; Ali Tajuddin, Hanifah Haydar (CLJ Publication, 2020)
It will be observed that in dispute resolution, conciliation is a first step process employed by the Syariah courts in that the parties will have to attempt amicable settlement of their dispute and only when it has failed to reach a settlement, would the case be listed for hearing in cour